Impact of digital newspapers on electoral vote - Paz Panduro, David Anibal (2020)
The purpose of this article is to demonstrate that the appearance of political candidates in digital newspapers has a positive correlation with electoral vote. The indicator of the independent variable used is the number of news stories in the digital press in which political candidates appear; whereas the indicator of the dependent variable is the percentage of the electoral vote obtained by the political candidates. The electoral process analyzed was the 2018 Lima Metropolitana Municipal Election. In addition, the Google search engine was used, where the basic command (search operator) site was used to search the websites of 19 Peruvian digital newspapers for the appearances of candidates in a semi-manual way. Finally, it was concluded that digital newspapers have a very strong correlation with electoral vote, as the Spearman’s rho coefficient obtained was 0.933.